Effects of corn supplementation into PKC-urea treated rice straw basal diet on hematological, biochemical indices and serum mineral level in lambs - Saeed, Osama Anwer; Sazili, Awis Qurni; Akit, Henny; Alimon, Abdul Razak; Samsudin, Anjas Asmara @ Ab Hadi (MDPI, 2019)
Twenty-seven Dorper lambs were used to determine the effect of supplementing corn as a source of energy into the palm kernel cake (PKC) urea-treated rice straw basal diet on the blood metabolic profile and metals in lambs. The lambs were randomly allotted to three experimental treatments according to their initial body weight for a 120 day trial. Dietary treatments were: T1 (control diet) = 75.3% of PKC + 0% corn, T2 = 70.3% of PKC + 5% corn, and T3 = 65.3% of PKC + 10% corn. The results of this study indicated that copper (Cu), selenium (Se), zinc (Zn), and iron (Fe) concentration intake, retention, and its absorption from the gut and apparent mineral digestibility were highly significant for the levels of corn supplementation. The biochemical and hematological parameters remained within normal levels with the treatments, but the white blood cell, eosinophil count, cholesterol, and low-density lipoprotein cholesterol (LDL) were significantly higher in T3. Treatment 3 significantly increased the concentration of Se and Fe, while Zn was reduced in the blood serum of lambs on day 120. The result shows that the inclusion of corn has no effect on the hematological and biochemical parameters of lambs after incorporating corn into the PKC-based diet at 5% and 10%.